5′-AMP Activated Protein Kinase is Involved in the Regulation of Myocardial β-Oxidative Capacity in Mice - Stride, Nis; Larsen, Steen; Treebak, Jonas T.; Hansen, Christina N.; Hey-Mogensen, Martin; Speerschneider, Tobias; Jensen, Thomas E.; Jeppesen, Jacob; Wojtaszewski, Jørgen F.; Richter, Erik A.; Køber, Lars; Dela, Flemming (Frontiers in Physiology, 2012)
5'-adenosine monophosphate-activated protein kinase (AMPK) is considered central in regulation of energy status and substrate utilization within cells. In heart failure the energetic state is compromised and substrate metabolism is altered. This may be linked to changes in AMPK-activity. We investigated mitochondrial oxidative phosphorylation capacity from the oxidation of long- and medium-chain fatty-acids (LCFA and MCFA) in cardiomyocytes from young and old mice expressing a dominant negative AMPKα2 (AMPKα2-KD ) construct and their wildtype (WT) littermates. We found a 35-45 % (P<0.05) lower mitochondrial capacity for oxidizing MCFA in AMPKα2-KD of both age groups, compared to WT. This coincided with marked decreases in protein expression (19%/29%, P<0.05) and activity (14%/21%, P<0.05) of 3-hydroxyacyl-CoA-dehydrogenase (HAD), in young and old AMPKα2-KD mice, respectively, compared to WT. Maximal LCFA-oxidation capacity was similar in AMPKα2-KD and WT mice independently of age implying that LCFA-transport into the mitochondria was unaffected by loss of AMPK activity. Expression of regulatory proteins of glycolysis and glycogen breakdown showed equivocal effects of age and genotype. The results show that AMPK is necessary for normal mitochondrial function in the heart. The data indicate that decreased AMPK activity may lead to an altered energetic state of the heart which could contribute to cardiac metabolic remodeling as seen in heart failure.